Identifikasi Komoditas Unggulan Pertanian Kecamatan Bandar, Kabupaten Batang, Jawa Tengah - Simamora, Liska; Fauziah, Irma; Novitaningrum, Restie; Fadhilah, Muhammad Luthfie (Universitas Veteran Bangun Nusantara, 2025)
This study aims to identify the leading agricultural commodities in Bandar Subdistrict, Batang Regency, Central Java, using the Location Quotient (LQ) method. The background of this research is based on the absence of clear specialization in agricultural commodities in Bandar, despite its agroecological potential. The data used include harvested area statistics for major food crops such as rice, maize, cassava, sweet potatoes, and peanuts. The LQ method measures the comparative advantage of a commodity by comparing its share of harvested area at the subdistrict level with that at the regency level. The results reveal that four commodities namely maize (LQ=1.2), cassava (LQ=3.2), sweet potatoes (LQ=8.8), and peanuts (LQ=5.6) are categorized as leading commodities. Each of these demonstrates regional specialization and is supported by factors such as agroclimatic suitability, farming experience, input availability, and market demand. Conversely, rice has an LQ value of 0.7, indicating it is not a leading commodity in the area due to limited water infrastructure. This research provides valuable insights for policymakers in designing development strategies that are focused and sustainable. The findings contribute to improving the effectiveness of agricultural planning and optimizing resource allocation, ultimately supporting farmer welfare and local economic resilience through the strengthening of agribusiness potential.